2020
DOI: 10.3390/en13215628
|View full text |Cite
|
Sign up to set email alerts
|

Ratepayer Perspectives on Mid- to Large-Scale Solar Development on Long Island, NY: Lessons for Reducing Siting Conflict through Supported Development Types

Abstract: The state of New York has ambitious mandates for reducing greenhouse gas emissions and increasing renewable energy generation. Solar energy will play an important role in reducing greenhouse gas emissions from the electric energy sector. Concerns over solar installations’ impacts to host communities and the environment have led to growing conflicts over solar energy siting on Long Island, in other parts of New York, and throughout the US. Understanding community members’ perspectives is critical for reducing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Based on previous theoretical and empirical studies related to social acceptance of renewable energy (RE) (e.g., Walker, 1995;van der Horst, 2007;Ansolabehere & Konisky, 2009;Sovacool, 2009;Batel et al, 2013;Fast, 2013), it is anticipated that successful deployment of agrivoltaics will necessitate sensitivity to and accommodation of public perceptions, especially rural perceptions, related to solar infrastructure on farmland. While majority of research related to social acceptance of RE is focused on wind (e.g., Wüstenhagen et al, 2007;Gross, 2007;Firestone et al, 2007Firestone et al, , 2009Firestone et al, , 2015Mulvaney et al, 2013;Bessette & Mills, 2021) and less so on solar (Carlisle et al, 2014(Carlisle et al, , 2015(Carlisle et al, , 2016Sovacool & Ratan, 2013;Schelly et al, 2020), the general concepts and factors identified as influential of support can be applied to develop a framework for understanding factors that may play a role in shaping public perceptions about agrivoltaic systems.…”
Section: Previous Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on previous theoretical and empirical studies related to social acceptance of renewable energy (RE) (e.g., Walker, 1995;van der Horst, 2007;Ansolabehere & Konisky, 2009;Sovacool, 2009;Batel et al, 2013;Fast, 2013), it is anticipated that successful deployment of agrivoltaics will necessitate sensitivity to and accommodation of public perceptions, especially rural perceptions, related to solar infrastructure on farmland. While majority of research related to social acceptance of RE is focused on wind (e.g., Wüstenhagen et al, 2007;Gross, 2007;Firestone et al, 2007Firestone et al, , 2009Firestone et al, , 2015Mulvaney et al, 2013;Bessette & Mills, 2021) and less so on solar (Carlisle et al, 2014(Carlisle et al, , 2015(Carlisle et al, , 2016Sovacool & Ratan, 2013;Schelly et al, 2020), the general concepts and factors identified as influential of support can be applied to develop a framework for understanding factors that may play a role in shaping public perceptions about agrivoltaic systems.…”
Section: Previous Researchmentioning
confidence: 99%
“…There is a scarcity of empirical research directly aimed at identifying factors that influence support or opposition to solar PV development in the U.S. (exceptions include Carlisle et al, 2014Carlisle et al, , 2015Carlisle et al, , 2016Schelly et al, 2020). These studies have found rural residency (Carlisle et al, 2014(Carlisle et al, , 2016, land type (Carlisle et al, 2016;Schelly et al, 2020) and distribution of economic benefits (Schelly et al, 2020) to have strong influence on public perceptions related to solar projects. A survey by Carlisle et al (2016) found that rural residents are more likely to oppose local solar development than urban residents, suggesting that rural communities perceive land use differently.…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations